Pengaruh Kegiatan Supervisi Pendidikan yang Dilakukan oleh Kepala Sekolah terhadap Kemampuan Mengajar Guru - Maisyaroh Maisyaroh (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The study aimed to investigate teachers’ teaching competence, supervision carried out by principals, and the effect of the supervision on teachers’ competence. This descriptive-correlational study involved a population of 989 teachers of all public junior high schools in Malang. Ten schools were randomly selected; then, proportional random sampling was employed to select the teachers from each school. A questionnaire and observation were used to collect the data, which were analyzed using mean statistics and linear regression. The findings show that teachers’ competence was of good category, that supervision by principals was of fair category, and that the supervision had a predicting power of 43.5% to improve teachers’ competence.